Peripheral Nervous System Involvement in Sjögren’s Syndrome: Analysis of a Cohort From the Italian Research Group on Sjögren’s Syndrome - Cafaro, Giacomo; Perricone, Carlo; Carubbi, Francesco; Baldini, Chiara; Quartuccio, Luca; Priori, Roberta; Berardicurti, Onorina; Ferro, Francesco; Gandolfo, Saviana; Gattamelata, Angelica; Giacomelli, Roberto; De Vita, Salvatore; et al. (Frontiers in Immunology, 2021)
Purpose. The reported prevalence of peripheral nervous system (PNS) involvement in primary Sjögren’s syndrome (pSS) has been reported to range from 2% to over 50%. Bias in study designs, including low number of patients and unclearly defined rheumatological and neurological diagnosis could explain such variability. Consequently, the exact depiction of PNS involvement in pSS is still lacking. This study aimed at analyzing the prevalence and the clinical and laboratory factors associated with PNS involvement in a very large cohort of well-characterized pSS patients with a clearly defined neurological diagnosis. Methods. Clinical and serological data of 1,695 pSS patients with specific and accurate information on PNS involvement were analyzed. Comparisons between patients with and without PNS involvement and between patients with distinct subsets of PNS manifestations were performed. Results. Prevalence of PNS involvement was 3.7%. The most frequent types observed were pure sensory neuropathies and axonal sensorimotor polyneuropathies (SMP). Patients with PNS involvement exhibited a more active disease profile and were more frequently treated with immunosuppressants. Intriguingly, clinical and serological negative prognostic factors, including purpura, extra-glandular manifestations, leukopenia, low complement and cryoglobulinaemia, principally characterized patients with SMP, while subjects with pure sensory neuropathy displayed a milder phenotype. Conclusion. Our results highlight that PNS involvement is rather rare, but prognostically relevant in pSS. Main adverse prognostic features characterize patients with SMP, while pure sensory neuropathies are usually associated with a mild clinical picture. These findings, useful for patient stratification, may suggest protean pathogenic pathways underlying different types of PNS manifestations in pSS.